Standardised protocol for a prospective cross-sectional multicentre clinic-based evaluation of two dual point-of-care tests for the screening of HIV and syphilis in men who have sex with men, sex workers and pregnant women - Cordioli, Maddalena; Gios, Lorenzo; Mirandola, Massimo; Zorzi, Antonella; Barbara, Christopher; Padovese, Valeska; Hançali, Amina; Oumzi, Hicham; Caceres, Carlos; Vargas, Silver; Kularatne, Ranmini; Mwima, Simon; et al. (BMJ open, 2020)
IntroductionDual point-of-care tests (POCTs) for detecting antibodies to HIV and syphilis have been developed for use with venous whole blood, serum/plasma or finger-prick capillary whole blood. Several tests are commercially available showing encouraging performance compared with ‘gold-standard’ reference tests in laboratory-based studies. However, data on their performance in the field are limited. This prospective cross-sectional study will conduct a clinic-based evaluation to assess the performance characteristics and acceptability to end-users of two dual HIV/syphilis POCTs for the screening of HIV and syphilis among men who have sex with men (MSM), sex workers (SWs) and pregnant women (PW). This master protocol outlines the overall research approach that will be used in seven countries.Method and analysisMSM, SWs and PW presenting at clinic evaluation sites in high, low and middle-income countries will be enrolled. The (WHO preapproved) POCTs to be evaluated are SD Bioline HIV/Syphilis Duo (Abbott) and Dual Path Platform HIV-Syphilis Assay (Chembio). Finger-prick blood will be collected to perform POCTs and compared with laboratory results (venepuncture blood). Procedures will be carried out by trained healthcare staff and tests performed according to the manufacturers’ directions. Sample size was calculated based on local prevalence of HIV and syphilis. The sensitivity, specificity, positive and negative predictive values for each POCT will be calculated. The study is ongoing with recruitment expected to be completed in all countries by mid to late 2021.Ethics and disseminationThis core protocol was independently peer reviewed and approved by the Research Project Review Panel (RP2) of the WHO Department of Sexual and Reproductive Health and Research and by the WHO Ethics Review Committee (ERC). The protocol has been adapted to individual countries and approved by RP2, ERC and institutional review boards at each site. Results will be disseminated through peer-reviewed journals and relevant conferences.